Towards a Global Administrative Space in Climate Governance? Mapping the Embeddedness of International Environmental Bureaucracies - Jörgens, H.; Saerbeck, B.; Well, M.; Kolleck, N. (59th Annual Convention of the International Studies Association “Power of Rules and Rule of Power”, 2018)
Based on a unique dataset derived from a large-scale online survey among the participants of recent Conferences of the Parties under the United Nations Framework Convention on Climate Change (UNFCCC), the paper maps the full network of actors in global climate change policy. Applying methods of social network analysis (SNA), we assess the relative centrality and importance of different actor groups (national governments, international bureaucracies, NGOs, business, research, and others). The main aim of the paper is to explore whether international environmental bureaucracies occupy a central role in the global climate policy network that enables them to communicatively link different actor groups, thereby fulfilling a bridging or brokering function in international climate governance.